USP Escuela de enfermería y el Programa de Inclusión Social: un enfoque histórico. - Pereira Dias, Rayana; Fernandes de Freitas, Genival; Barrionuevo Bonini, Bárbara (Cultura de los Cuidados, 2020)
In the early days of Brazilian nursing, the best category to build the profession was sought: white women. The color of one skin was an impediment to study nursing. At the Nursing School of University of São Paulo (EEUSP), there was never an official mechanism to bar black people from taking the course, but even so, it has always trained a small number of black students. With USP's Social Inclusion Program (Inclusp), in 2007, the expectation was to expand access to the University for this particular group of people. That is why, this study was based on the hypothesis that few black nurses graduate EEUSP still, compared to the white majority who enter the course each year. Goals: Identify whether EEUSP continues to train few black nurses, even with affirmative action, and describe the experience of black and brown school students and alumni. Method: First, it sought to map how many benefited from the program and who these people were; then, some of these black graduates were invited to tell their stories and experiences as a student. Results: The color underreporting in the studied documentation compromised the results. There were five descriptive interviews. Conclusions: That despite the program, EEUSP continues to train few black nurses, contributing to the fact that, until today, the number of black nurses trained by public institutions remain small.